Pigmen Klorofil Pada Mikroalga Coccolithophore sp. Hasil Kultivasi Pada Skala Laboratorium - Ngabalin, Daniel; Putnarubun, Cenny; Metungun, Jakomina; Ngabalin, Dewy Rosi (Jambura Fish Processing Journal, 2025)
Microalgal pigments are important bioactive compounds with potential applications in the food, pharmaceutical, and cosmetic industries. Coccolithophore sp., a type of marine microalga, is known to contain pigments such as carotene, chlorophyll, and xanthophyll. This study aims to identify the types of pigments present in Coccolithophore sp. using column chromatography. The extraction process was carried out using 90% acetone, followed by pigment separation with a stepwise eluent ratio of hexane:acetone (4:1 to 1:4). The separation results revealed the presence of carotene (yellow), chlorophyll a (dark green), chlorophyll b (light green), and xanthophyll (light yellow) pigments. Elution times varied depending on the polarity of each compound. These results demonstrate the potential of Coccolithophore sp. as a natural pigment source for environmentally friendly industrial applications.